Adaptive IDA-PBC for underactuated mechanical systems with constant disturbances - Franco,E (International Journal of Adaptive Control and Signal Processing, 2019)
This work investigates the control of nonlinear underactuated mechanical systems with matched and unmatched constant disturbances. To this end, a new control strategy is proposed, which builds upon the interconnectionanddampingassignment passivitybased control, augmenting it with an additional term for the purpose of disturbance compensation. In particular, the disturbances are estimated adaptively and then accounted for in the control law employing a new matching condition of algebraic nature. Stability conditions are discussed, and for comparison purposes, an alternative controller based on partial feedback linearization is presented. The effectiveness of the proposed approach is demonstrated with numerical simulations for three motivating examples: the inertia wheel pendulum, the diskondisk system, and the pendulumoncart system.